Biomass fly ash effect on fresh and hardened state properties of cement based materials. (August 2015) - Rajamma, R.; Senff, L.; Ribeiro, M.J.; Labrincha, J.A.; Ball, R.J.; Allen, G.C.; Ferreira, V.M.
Abstract: Cement pastes and mortars were prepared by replacing ordinary Portland cement with different dosages of biomass fly ashes (0, 10, 20 and 30% BFA) whilst in dry condition. The effect of BFA on the flow behaviour (spread on table and rheology), setting time, temperature of hydration and electrical resistivity was studied in this experimental research. Increasing the amount of BFA in the compositions required extra dosage of water, as a result of particles fineness, tendency for agglomeration and retention/absorption of water molecules. As a consequence, the relative amount of free water diminishes and the flowability is poorer. The introduction of BFA also led to an increase in setting time, while the resistivity obtained from the impedance measurements tends to be lower than the reference paste (ash-free). The higher concentration of mobile species in the pore solution, namely sodium ions introduced by the ash, explains that tendency. The hydration temperature of cement pastes tends to decrease with the level of cement to ash replacement. Between the two tested ashes (from grate and fluidized sand bed furnaces), differences in particle size and shape, in the amount of residual organic matter and concentration of inorganic components define minor changes in the workability and setting behaviour. Therefore, the introduction of biomass fly ashes affects the hardened state features but do not compromise them.